Curcumin A Better Medicine to Treat Coronavirus- A Review - Taanya Imtiaz1 , Dinesh Premavathy, Kavitha.S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Curcumin, a yellow pigment, which is a bioactive compound in Turmeric, is a polyphenol derivative used asan herbal medicine to treat remedies. Coronavirus disease-2019 (COVID-19) is caused due to coronaviruswhich is an infectious and dangerous virus. Coronavirus causes severe infections in humans and also indifferent species of animals. Curcumin has multi properties in which one of them is anti-viral, which mayhelp in the prevention and treatment of COVID-19. Curcumin can be taken by the means of food andstudies show that there are no side effects, caused due to its consumption. Turmeric is the main source ofCurcumin; RDA of Curcumin is 3mg/kg/day. Some of its properties include: anti-viral, anti-inflammatory,anti-bacterial, anti-parasitic, anti-tumor, anti-microbial activities. It also has the ability to gene transcriptionthe viral strains like coronavirus, and maybe a possible treatment in treating COVID-19. Curcumin asexhibits anti-viral properties and acts on viral strains for gene transcription, can be a possible treatment inprevention and treating COVID-19.